STUDENTS PERCEPTION OF INTEGRATED EMPATHY COUNSELOR PERSONALITY IN SENIOR HIGH SCHOOL IN KEDIRI CITY: A QUALITATIVE DESCRIPTIVE STUDY - Galang Surya Gumilang (Universitas Negeri Surabaya, 2025)
This research was conducted while becoming a field work practice supervisor at one of the senior high schools in Kediri City, some students stated that the Counselor did not have empathy as evidenced by the behavior and facial expressions of the counselor. Therefore, according to the facts in the field, the focus of the research taken was